Motivation as Mediator between Family Support to the Readiness of Pregnant Woman in Exclusive Breastfeeding - Sri Mulyani; A. A. Subiyanto; Sapja Anantanyu; Supriyadi Heri Respati; Budiyanti Wiboworini (Intelektual Pustaka Media Utama, 2017)
The success of the implementation of exclusive breastfeeding in the community is depend on the readiness of pregnant mothers in exclusive breastfeeding. This readiness is influenced by several factors including motivation and support exclusive breastfeeding by family. This study aimed to examine the empirical model that shows the motivational role as mediators of the relationship between family support of readiness pregnant mothers in exclusive breastfeeding. Cross-sectional study performed on pregnant women in Surakarta. A sample of 150 respondents mother in her first time pregnancy. The closed questionnaire of Likert scale developed to measure three variables of the study. Path analysis procedure used to test the hypothesis of motivational role as mediator relations between two other variables. The results showed that all three variables had a significant relation (p <0.001). The relationship between family support to readiness pregnant women after entering motivation as covariates remained significant but decreased significantly path coefficient (β = 0.365; p <0.001 becomes β = 0.260; p = 0.001). Thus the motivation become a mediator relationship with the family support of readiness pregnant mothers in exclusive breastfeeding.